Composition and Density of Seagrass Species in Tanjung Aan Coastal Waters, Central Lombok - Ningsih, Resthi Maryati; Larasati, Chandrika Eka; Wahyudi, Rhojim (Jurnal Biologi Tropis, 2025)
Seagrasses are flowering plants (Angiosperms) with a wide distribution along the world's coastlines, including the Indo-Pacific region where 15 species are found in Indonesian waters. Seagrass beds play important ecological roles, such as stabilizing sediments, providing habitat for marine organisms, and contributing to nutrient cycling in marine ecosystems. This study aims to identify seagrass species, composition, and density in the coastal waters of Tanjung Aan, Central Lombok, to support sustainable coastal ecosystem management efforts. The method used was Line Transect with quadrat sampling, along with measurements of water quality parameters and sediment grain size analysis. The results showed differences in composition and community structure between two observation stations. Station 1 was dominated by S. isoetifolium and C. rotundata with a simple community structure, while Station 2 was more diverse with a dominance of C. rotundata and E. acoroides, reflecting more stable and sheltered habitat conditions. The highest seagrass density was found in S. isoetifolium. This study provides important baseline data for the conservation of seagrass ecosystems in the coastal areas of Lombok Island.